The IPCC and treatment of uncertainties: topics and sources of dissensus. (7th July 2014) - Adler, Carolina E.; Hirsch Hadorn, Gertrude
<x xml:space="preserve">Abstract</x> Characterizing uncertainty in the assessment of evidence is common practice when communicating science to users, a prominent example being the Intergovernmental Panel on Climate Change (IPCC) Assessment Reports (ARs). The IPCC guidance note is designed to assist authors in the assessment process by assuring consistent treatment of uncertainties across working groups (WGs). However, debate on this approach has surfaced among scholars on whether applying the guidance note indeed yields the desired consistent treatment of uncertainties thus facilitating effective communication of findings to users. The IPCC guidance note is therefore a paradigmatic case for reviewing concerns regarding treatment of uncertainties for policy. We reviewed published literature that outline disagreement or dissensus on the guidance note in the IPCC assessment process, structured as three distinct topics. First, whether the procedure is reliable and leads to robust results. Second, whether the broad scope of diverse problems, epistemic approaches, and user perspectives allow for consistent and appropriate application. Third, whether the guidance note is adequate for the purpose of communicating clear and relevant information to users. Overall, we find greater emphasis placed on problems arising from the procedure and purpose of the assessment, rather than the scope of application. Since a procedure needs to be appropriate for its purpose and scope, a way forward entails not only making deliberative processes more transparent to control biases. It also entails developing differentiated instruments to account for diversity and complexity of problems, approaches, and perspectives, treating sources of uncertainty as relevant information to users. WIREs Clim Change 2014, 5:663–676. doi: 10.1002/wcc.297 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.